Terminal residues of metolachlor in groundnut (Arachis hypogaea), soybean (Glycine max) and onion (Allium cepa) - TAMILSELVAN, C; SUNDARARAJAN, R (The Indian Journal of Agricultural Sciences, 2013)
An experiment Was conducted during January 1987-November 1990 to study the Lerminal residues of metolochlor arplied as a pre-emergence herbieidc in groundnut (Arachis hypogaea L.), soybean [Glycine max (L) Merr.] and onion (Allium cepa L.) The edible parts of groundnut and soybean and the soil did not contain any detectable residucs of metolachlor (<0.01 ppm) when applied @ 1 and 2 kg ai/ha, whereas onion bulbs contained traces of residues in 2 seasons (September-November 1989 and December-Murch 1990).